Simultaneous Characterization of Sympathetic and Cardiac Arms of the Baroreflex through Sequence Techniques during Incremental Head-Up Tilt - Marchi, Andrea; Bari, Vlasta; De Maria, Beatrice; Esler, Murray; Lambert, Elisabeth; Baumert, Mathias; Porta, Alberto (Frontiers in Physiology, 2016)
We propose a sympathetic baroreflex (sBR) sequence method for characterizing sBR from spontaneous beat-to-beat fluctuations of muscle sympathetic nerve activity (MSNA) and diastolic arterial pressure (DAP). The method exploits a previously defined MSNA variability quantifying the fluctuations of MSNA burst rate. The method is based on the detection of MSNA and DAP sequences characterized by the contemporaneous DAP increase and MSNA decrease or vice versa. The percentage of sBR sequences (SEQ%sBR) was taken as an indication of the degree of sBR solicitation and the average slope of the regression lines in the (DAP,MSNA) plane was taken as sBR sensitivity (sBRSSEQ) and expressed in bursts.s-1.mmHg-1. sBRSSEQ was compared to a more traditional estimate based on the baroreflex threshold analysis (sBRSBTA). An incremental head-up tilt protocol, carried out in 12 young healthy subjects (age: 20-36 yr, median = 22.5 yr, 9 females) sequentially tilted at 0°, 20°, 30°, 40°, 60° table inclinations, was utilized to set the sBR sequence method parameters. Traditional sequence analysis was exploited to estimate cardiac baroreflex (cBR) sensitivity (cBRSSEQ) and percentage of cBR sequences (SEQ%cBR). The head-up tilt induced the progressive increase of SEQ%sBR and SEQ%cBR and gradual decrease of both sBRSSEQ and cBRSSEQ, thus suggesting the gradual rise of the sBR and cBR solicitations and the progressive reduction of their effectiveness with the stimulus. sBRSSEQ was significantly associated with sBRSBTA. sBRSSEQ and cBRSSEQ were significantly correlated as well as SEQ%sBR and SEQ%cBR, even though the correlation was not strong, thus suggesting a certain degree of independence between the baroreflex arms. The proposed sBR sequence approach provides a dynamical characterization of the sBR alternative to more traditional static pharmacological and nonpharmacological methods and fully homogenous with the cBR sequence technique.